How Does Economic Policy Uncertainty (Epu) Impact Copper-Firms Stock Returns? International Evidence - Espinosa-Mendez, C (Elsevier Ltd, 2023)
Using monthly data, we study 43 copper firms between January 2011 and March 2022. We analyze how copper-firms stock returns depend on copper-spot prices returns. Nevertheless, the main contribution of this article is to study how changes in Global EPU (GEPU) and Local EPU may impact on copper-firms stock returns and how both of them may influence the sensitivity of stock returns to copper prices returns. We find that both GEPU and Local EPU have a statistically significant and negative impact on stock returns. We also study regimes of high and low levels of EPU (Global and Local). For high levels of GEPU we find a negative relationship between stock returns and GEPU and for low levels of GEPU we detect a positive relationship. We also consider how high levels and low levels of Local EPU impact the relationship between copper spot returns and stock returns. When there are high levels of GEPU the sensitivity of stock returns to copper spot returns increases and the opposite is verified when there are low levels of GEPU. Using Local EPU we do not find significant changes in the sensitivity of stock returns to copper spot returns. As robustness test, we consider firms from other four industries (Gold, Oil, Electric Distribution and Gas Distribution). Most of the results show different behavior in each industry regarding the association between EPU and stock returns. We also run the main equations considering a six-factor model for returns (five factors from Fama and French) and the momentum factor. Finally, we do the analysis for copper future returns (90 days and 15 months), reporting similar results. We do not find significant changes in the results after doing all the robustness checking. © 2023 Elsevier Ltd